1990
DOI: 10.1096/fasebj.4.13.2210157
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of cell growth to the regulation of tissue‐specific gene expression during osteoblast differentiation

Abstract: The relationship of cell proliferation to the temporal expression of genes characterizing a developmental sequence associated with bone cell differentiation can be examined in primary diploid cultures of fetal calvarial-derived osteoblasts by the combination of molecular, biochemical, histochemical, and ultrastructural approaches. Modifications in gene expression define a developmental sequence that has 1) three principal periods: proliferation, extracellular matrix maturation, and mineralization; and 2) two r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

52
552
4
6

Year Published

1996
1996
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 889 publications
(614 citation statements)
references
References 0 publications
52
552
4
6
Order By: Relevance
“…AP is broadly expressed in many pre-and postnatal tissues, and in different cell types such as osteoblasts 37 , embryonic stem cells 38 , bone marrow stroma cells 39 , liver and kidney cells 40 , granulocytes 41 and B cells 42 ; however, in postnatal mouse striated muscles, AP is expressed only by vessel-associated cells, in both endothelial cells and pericytes, as previously reported 9,[14][15][16] , and exhaustively confirmed in this work through a variety of histochemical and immunochemical methods. Most importantly, by using virtually all possible experimental approaches, we demonstrated that both AP and Cre expression are invariably absent in quiescent satellite cells, as well as in proliferating and differentiating myogenic cells in vitro or in vivo, even after cardiotoxin-induced damage.…”
Section: Discussionmentioning
confidence: 99%
“…AP is broadly expressed in many pre-and postnatal tissues, and in different cell types such as osteoblasts 37 , embryonic stem cells 38 , bone marrow stroma cells 39 , liver and kidney cells 40 , granulocytes 41 and B cells 42 ; however, in postnatal mouse striated muscles, AP is expressed only by vessel-associated cells, in both endothelial cells and pericytes, as previously reported 9,[14][15][16] , and exhaustively confirmed in this work through a variety of histochemical and immunochemical methods. Most importantly, by using virtually all possible experimental approaches, we demonstrated that both AP and Cre expression are invariably absent in quiescent satellite cells, as well as in proliferating and differentiating myogenic cells in vitro or in vivo, even after cardiotoxin-induced damage.…”
Section: Discussionmentioning
confidence: 99%
“…ALP gene expression has a two phase expression, in other words, two peaks of expression profiles, and some suggest that the first peak is strongly related to differentiation and that the second one may be related to mineral deposition (14,26). In our study, ALP gene expression of MSCs with type I collagen or type I collagen and fibronectin showed a peak level at day 12 and then decreased.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, ALP gene expression of MSCs with type I collagen or type I collagen and fibronectin showed a peak level at day 12 and then decreased. It was also repotted that the extracellularmatrix (ECM) supported the expression of tissue-specific genes during osteoblast differentiation and suppressed the proliferation of cells (14). Therefore, MSCs with type I collagen and type I collagen and fibronectin The expression of ALP mRNA and enzyme activity before the initiation of osteoblast mineralization suggests that ALP may be involved in preparing the ECM for an ordered deposition of minerals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations